Weed Management in Clover - Jason Ferrell; Brent Sellers; Pratap Devkota (EDIS)
This 4-page publication provides information on herbicides that can be applied for weed control in clover production systems. Written by J. A. Ferrell, B. A. Sellers, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised June 2020.